(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
A series of 11 experimental hydrological field surveys of the Daugava’s flood-flows has been conducted within the river-floodplain system of the Middle Daugava by the Department of Geography and Chemistry, Daugavpils University, in 2007-2017. The field surveys were conducted in a form of real-time Lagrangian drift experiments, which were focused on a continuous tracking and monitoring of pre-selected flood water masses moving along the Middle Daugava River from Krauja to Dunava at the peak of the spring floods. The real-time tracking and monitoring of the selected flood water masses was conducted by applying a manned drifting research platform. It was equipped with a GPS receiver and an echo-sounding device for repeated measurements of the average drift velocity, the channel's depth and geographical position of the platform in relation to its initial location. During the drift experiments, instrumental measurements were performed repeatedly, each 30-60 minutes. The obtained records were then used to analyze downstream changes in main hydraulic characteristics of the surveyed flood-flows. Main results of 9 real-time Lagrangian drift experiments conducted within the Middle Daugava river-floodplain system in 2007-2017 are analyzed and discussed in this paper. Application of the Lagrangian reference frame for the obtained data records revealed the unsteady, spatially varied nature of the surveyed flood-flows and highlighted an overall downstream reduction of their average drift velocities and depths, as they leaved the Baltic Moraine Uplands and entered the East Latvian Lowland downstream from Daugavpils. The Spearman’s correlation revealed the strong effect of inter-annual variation of the peak flood discharge and longitudinal gradient of the water surface on the main hydraulic characteristics of the flood-flows. Application of the well-known Chézy equation to the obtained data records also revealed its inadequacy for research purposes of this natural river-floodplain system, but also highlighted the importance of other factors (such as the active cross-section area and hydraulic interaction between the river and its floodplain) on the site-by-site variation of the current velocity within the main channel during the floods.